Level Up Pembelajaran Melalui Pendampingan Guru Dalam Pengembangan Game Edukatif Berbasis Gimkit Dan Quizwhizzer - Ning Mukaromah; Nailatul Khoiriyah Cholil (Saniya Institute, 2025)
The development of digital technology has driven a paradigm shift in education, demanding the integration of technology-based learning and the strengthening of 21st-century skills. However, the reality at Yayasan Pesantren Bina Mandiri Al Qodiriyah Srono Banyuwangi reveals limitations among teachers in utilizing digital media, a lack of learning innovation, and the absence of educational game integration in the teaching process. Based on these needs, this community service program aims to enhance teachers’ capacity through training and mentoring on the use of the Gimkit and Quizwhizzer applications. The program employs a Participatory Action Research (PAR) approach, involving teachers in all stages—problem identification, solution planning, implementation, and reflection. The results demonstrate a significant improvement in teachers’ skills in using interactive learning media, the establishment of a digital learning community, and increased student engagement and motivation. These positive changes are evident not only in technical aspects but also in the teachers’ transformational awareness of the importance of innovative technology-based learning. The findings affirm that digital learning transformation within pesantren environments is highly achievable when accompanied by a collaborative approach, continuous mentoring, and adequate institutional support